Future HAB science: Directions and challenges in a changing climate - Wells, Mark L.; Karlson, Bengt; Wulff, Angela; Kudela, Raphael; Trick, Charles; Asnaghi, Valentina; Berdalet, Elisa; Cochlan, William; Davidson, Keith; De Rijcke, Maarten; Dutkiewicz, Stephanie; Hallegraeff, Gustaaf; et al. (Harmful algae, 2020)
•HABs develop through the integration of physical, chemical, and temporal drivers.•We need a mechanistic understanding that reveals how climate affects these drivers.•Accelerating climate change in coastal regions signals the urgency for action.•New strategies, tools, and observatories for HABs will improve our forecast skill.•Focused research on subsets of HAB species would greatly accelerate advances. There is increasing concern that accelerating environmental change attributed to human-induced warming of the planet may substantially alter the patterns, distribution and intensity of Harmful Algal Blooms (HABs). Changes in temperature, ocean acidification, precipitation, nutrient stress or availability, and the physical structure of the water column all influence the productivity, composition, and global range of phytoplankton assemblages, but large uncertainty remains about how integration of these climate drivers might shape future HABs. Presented here are the collective deliberations from a symposium on HABs and climate change where the research challenges to understanding potential linkages between HABs and climate were considered, along with new research directions to better define these linkages. In addition to the likely effects of physical (temperature, salinity, stratification, light, changing storm intensity), chemical (nutrients, ocean acidification), and biological (grazer) drivers on microalgae (senso lato), symposium participants explored more broadly the subjects of cyanobacterial HABs, benthic HABs, HAB effects on fisheries, HAB modelling challenges, and the contributions that molecular approaches can bring to HAB studies. There was consensus that alongside traditional research, HAB scientists must set new courses of research and practices to deliver the conceptual and quantitative advances required to forecast future HAB trends. These different practices encompass laboratory and field studies, long-term observational programs, retrospectives, as well as the study of socioeconomic drivers and linkages with aquaculture and fisheries. In anticipation of growing HAB problems, research on potential mitigation strategies should be a priority. It is recommended that a substantial portion of HAB research among laboratories be directed collectively at a small sub-set of HAB species and questions in order to fast-track advances in our understanding. Climate-driven changes in coastal oceanographic and ecological systems are becoming substantial, in some cases exacerbated by localized human activities. That, combined with the slow pace of decreasing global carbon emissions, signals the urgency for HAB scientists to accelerate efforts across disciplines to provide society with the necessary insights regarding future HAB trends.